2017
DOI: 10.1002/adv.21881
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical co‐deposition and characterization of polyaniline and manganese oxide nanofibrous composites for energy storage properties

Abstract: Ion diffusion rate and contact surface area of conducting polymers increased by composite formation with nanometric-size materials make them promising materials in the fabrication of energy storage devices. In this work, electronically conducting polyaniline and manganese oxide (PANI/MnO 2 ) nanofibrous composites were electrochemically co-deposited on stainless steel from binder-free electrolyte solution. Structural characterization and morphological characterization of the materials were performed with Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…As the typical representative, supercapacitors (SCs) have widely aroused scientific and technological interests due to their high-power output, fast charge-discharge kinetics, and long cycle life [8][9][10]. These advantages make them become the favorable candidates for applications of portable electronic device or hybrid electric vehicles [11,12]. Nonetheless, inferior energy density of SCs has hindered their extensive application in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…As the typical representative, supercapacitors (SCs) have widely aroused scientific and technological interests due to their high-power output, fast charge-discharge kinetics, and long cycle life [8][9][10]. These advantages make them become the favorable candidates for applications of portable electronic device or hybrid electric vehicles [11,12]. Nonetheless, inferior energy density of SCs has hindered their extensive application in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Further increase in current density resulted in a considerable loss of capacitance. A possible reason is the slight existing kinetic differences in the oxidation and reduction processes [ 22 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…SEM results and the digital photographs also confirmed that PAM penetrated the porous structure of the cellulose network ( Figure 2 b,c). The prepared CN/PAM composite was employed as an anode, and the in situ deposition of PANI was conducted through the electrochemical oxidation polymerization of aniline [ 19 ]. A large amount of green PANI was deposited on the cross section of the CPP composite hydrogel ( Figure 2 d).…”
Section: Resultsmentioning
confidence: 99%